Hemodynamic changes after acute fluid loading in patients with systemic sclerosis without pulmonary hypertension. (1st December 2018) - D'Alto, Michele; Romeo, Emanuele; Argiento, Paola; Mattera Iacono, Agostino; Vettori, Serena; Riccardi, Antonella; Allanore, Yannick; D'Andrea, Antonello; Rea, Gaetano; Bossone, Eduardo; Valentini, Gabriele; Naeije, Robert; et al.
Abstract : A fluid challenge with a rapid infusion of saline helps to discriminate between pre‐ and post‐capillary pulmonary hypertension (PH) and allows unmasking hidden post‐capillary PH. Systemic sclerosis (SSc) patients may present with biventricular systolic and diastolic dysfunction. The aim of this study was to evaluate the hemodynamic changes of the pulmonary circulation in SSc patients without PH after a fluid challenge. Twenty‐five SSc patients and 25 controls underwent right heart catheterization in basal conditions and after volume loading with saline infusion of 7 mL/kg over 5–10 min. At baseline, there was no difference in hemodynamics between SSc patients and controls. Rapid volume loading resulted in a significant increase in pressures and flows in both groups. Increases in right atrial pressure (3 ± 1 vs. 2 ± 1 mmHg, P  = 0.03), mean pulmonary artery pressure (5 ± 1 vs. 3 ± 1 mmHg, P  < 0.001), and pulmonary artery wedge pressure (PAWP; 5 ± 2 vs. 3 ± 1 mmHg, P  < 0.001) were larger in SSc patients than in controls. Conversely, cardiac index (0.4 ± 0.2 vs. 0.6 ± 0.3 L/min/m 2, P  = 0.005) increased less in SSc patients than in controls. Pulmonary vascular resistance did not differ between groups before and after volume loading. Four SSc patients and only one of the controls reached a PAWP > 18 mmHg suggesting latent left heart failure. Even if differences are small and not diagnostic for heart failure, SSc patients without PH have a larger increase in pulmonary vascular pressures and a smaller increase in cardiac output than controls after an acute volume loading, probably due to subclinical left ventricular diastolic dysfunction.